Principles for the development of clinical guidelines for Prevention & control of Cardiovascular diseases - Regmi, Prakash Raj (Nepalese Heart Journal, 2006)
According to WHO Cardiovascular disease (CVD) is the world’s biggest killer taking away lives of 17.5 Million people annually, As 80% of CVD-related mortality now occurs in countries with developing economies, it is imperative that governments in such countries work in partnership with Cardiac Societies and Heart Foundations to develop guidelines that reflect national priorities and resources.